Organization, atmosphere, and digital technologies: Designing sensory order. (September 2019) - Jørgensen, Lydia; Holt, Robin
We argue technology and organization are inherently spatial phenomenon. We conceptualize this conjunction as atmosphere: a gathering of mood, human practice, material and environmental conditions, and values that has sufficient coherence and distinction to constitute a distinct interior. Atmospheres, however, are not entirely stable and present: the interior is porous to outside influence, and the interior is never wholly ordered. We show this through the study of digitally mediated architectural design practice. We find the technological mediation of atmospheres is constituted in sensory and affective spatial arrangements, and not in rationally calculated configurations of assets and goals. An atmosphere is inherently aesthetic. This allows us to gesture toward a definition of organization as technologically mediated spatial struggle to reconcile interior coherence with outward exposure.